Lighting design for public spaces using innovative luminescent technologies - Alessandro Spennato (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
For several years, urban lighting has been regarded as a functional tool that can only guarantee safety and orientation for citizens. In addition to safety and light pollution, a phenomenon that has been at the centre of numerous debates for several years now, there is everything to do with saving energy and reducing the costs of urban lighting. Reducing even some of the considerable consumption of energy resources would benefit both economically and ecologically. Research led to the identification of space in the Abruzzo region. After analysing the park's current state, the question was asked: how can the garden be redeveloped by paying attention to ecological aspects and new technologies? The project aims to intervene in specific areas of the park to redevelop the context under analysis through new technologies, stimulating a new awareness of the lighting culture of spaces.